Food and lifestyle guidelines for people experiencing heartburn - Usai, Tecklah (Globalfora Research Group (GRG), 2021)
This book is a collection of food suitable for people who experience heartburn. More than fifty recipes (for the sort of stuff you)one can make for (your)oneself, family and friends. A well balanced diet that is suitable for people who are prone to Gastroesophageal Reflux Disease (GERD). In this book GERD gastroaesophageal Reflux disease) will be used interchangeably(e) with heartburn. The proportion spent on food will vary according to the size of the income, the standard of living, the time available for shopping and the numbers to feed. A considerable saving can be effected if fresh fruit and vegetables can be grown in the garden, manpower(. Food for those who are prepared) to preparethe food (take care) and effort to produce real meals suitable for people who experience heartburn (Johnson et al, 2004).